LIVER METABOLIC EFFECTS OF A HIGH-FAT LOW- CARBOHYDRATE DIET IN RATS: A STUDY UNDER DIFFERENT ENERGY CONDITIONS (Arquivos do Mudi, 2023)
The beneficial effects of high-fat, low-carbohydrate (HFLC) diets on glucose metabolismhave been questioned and its effects on liver metabolism are not totally clear. This workaimed to evaluate the HFLC diet effects under different energy conditions on glucosehomeostasis, fatty liver development and hepatic gluconeogenesis using the isolated perfusedrat liver. HFLC diet (79% fat, 19% protein, and 2% carbohydrates in Kcal%) wasadministered to rats over four weeks under three conditions: hypercaloric; isocaloric andhypocaloric (energy reduction of 20%). Fasting blood glucose levels and total fat in the liverwere higher in all HFLC diet rats. Oral glucose tolerance was impaired in isocaloric andhypercaloric groups, although insulin sensitivity wasn´t altered. HFLC diet also causedmarked liver metabolic alterations: higher gluconeogenesis rate from lactate and a reducedcapacity to catabolize alanine, the latter effect more intense in the hypocaloric condition. Weconcluded that, even when HFLC diets are used for weight loss, our data imply that they canpotentially cause harmful consequences for the liver.